Analysis of regulating activities of 5′-epiequisetin on proliferation, apoptosis, and migration of prostate cancer cells in vitro and in vivo - Xueni Wang; Xiaowei Luo; Xia Gan; Xia Gan; Chunmei Chen; Zaizhun Yang; Jing Wen; Wenxuan Fang; Hailing Huang; Chenghai Gao; Xuefeng Zhou; Xiaotao Feng; et al. (Frontiers in Pharmacology, 2022)
Advanced prostate cancer has a poor prognosis, and it is urgent to develop new effective drugs. 5′-Epiequisetin is a tetramic acid derivative which was isolated from a marine sponge-derived fungus Fusarium equiseti in our previous study. In this study, 5′-epiequisetin showed cytotoxicity against four prostate cancer cell lines, namely, LNCaP, 22Rv1, DU145, and PC-3 cells, with the lowest IC50 value of 4.43 ± 0.24 μM in PC-3 cells. Further studies showed that it could dramatically regulate the clonal colony formation, apoptosis, and migration of PC-3 cells. In addition, flow cytometry data showed that 5′-epiequisetin could block the cell cycle at the G1 phase. Proteome profiler array and Western blot revealed that 5′-epiequisetin could regulate the expression of proteins responsible for cell proliferation, apoptosis, and migration. 5′-Epiequisetin regulated the expression of PI3K, Akt, phosphorylated Akt, and proteins which control the cell cycle. Meanwhile, 5′-epiequisetin upregulated expression of DR5 and cleave-caspase 3, which play important roles in the process of apoptosis. Moreover, when DR5 was silenced by small interfering RNA, the proportion of apoptotic cells induced by 5′-epiequisetin remarkably declined. In addition, 5′-epiequisetin downregulated the expression of survivin which plays a key role in the process of survival and apoptosis. 5′-Epiequisetin also impacted beta-catenin and cadherins, which were associated with cell migration. In addition, 5′-Epiequisetin significantly inhibited the progression of prostate cancer in mice, accompanied by regulating the protein expression of DR5, caspase 8, survivin, and cadherins in vivo. Taken together, these findings indicated that 5′-epiequisetin showed an anti–prostate cancer effect by inducing apoptosis and inhibiting cell proliferation and migration both in vitro and in vivo, suggesting a promising lead compound for the pharmacotherapy of prostate cancer.